Merangkai Transformator Hubungan Segitiga-Bintang dan Bintang-Segitiga pada Jam Gasal - Sugijono, Sugijono (JTET (Jurnal Teknik Elektro Terapan), 2017)
A three phase transformator basicly consists of three single phase transformators with the primary winding connected  in either delta or star, and the secondary winding also connected  in either delta or star. The polarity of the magnetic flux in either primary or secondary winding of the single phase transformator has to be determined before connecting into a three phase transformator. The transformators with delta-star (Delta-Wye) and star-delta (Wye-Delta) connection only applied to odd clocks. The phase shift between vectors of primary and secondary voltages  is 30°per hour. The equation of the clock voltage vector are the same for either the delta-star transformator or the star-delta transformator at the same clock. The drawing of the vector voltage uses minute needle which always points to figure 12 to represent the high voltage primary winding, and the hour needle which points to figures other than 12 to represent the low voltage secondary winding. In drawing the circuit of the three phase transformnator should always follow the drawing of the voltage vector.Key words : delta and star connection, odd clock, transformator